PEMBUATAN CHROME EXTENSION UNTUK AKSES WEBSITE SISTEM KOMPUTER UNIVERSITAS DIPONEGORO - Teguh Martono, Kurniawan (Proceedings of KNASTIK, 2012)
Development of Internet technology have evolved over time. This development led to thedevelopment of the current number of Internet users . The amount was fantastic at theend of March 2011 where the total number of Internet users is approximately6,930,055,154 users. The number of users has also resulted in competition in thedevelopment of a web browser that will be used by internet users. Some web browsersare a favorite on the Internet is Mozilla, Google Chrome and Internet Explorer.Chrome extension is an application that can be developed by any developer who is toeffectiveness accessing the website This is because users no longer have trouble inaccessing a web page that is a favorite, because users can simply download the fileextensions and then installed into the web browse the chrome. This study refers to thefunction of the parts are there in the chrome extension of Diponegoro Universitycomputer system. The results obtained in this study was 100% of existing functions thatcan run in the browser google chrome.